Friendly fire : American images of the Vietnam War - Kinney, Katherine, 1959- (OUP E-Books., 2000)
Hundreds of memoirs, novels, plays, and movies have been devoted to the American war in Vietnam. In spite of the great variety of media, political perspectives and the degrees of seriousness with which the war has been treated, Katherine Kinney argues that the vast majority of these works share a single story: that of Americans killing Americans in Vietnam. Friendly Fire, in this instance, refers not merely to a tragic error of war, it also refers to America's war with itself during the Vietnam years. Starting from this point, this book considers the concept of ""friendly fire"" from multiple.